Road Development and Traffic Improvement in Informal Residential Areas: A Case Study of Kabul’s 13th District - Stanikzai, Ali Kaihan; Halimee, Mohammad Kamil; Sadeq, Mohammad Seddiq (Journal of Natural Sciences – Kabul University, 2025)
This study investigates the impact of newly connected main roads on traffic conditions in informal areas of Kabul. Using both quantitative and qualitative methods, indicators such as Level of Service (LOS), volume-to-capacity ratio (V/C), average speed, and network analysis in Geographic Information Systems (GIS) were assessed. The findings indicate that after the road connections, LOS improved from near-stable to stable, the V/C ratio decreased by 0.11, and average travel time was reduced by up to 15 minutes. GIS analysis confirmed reduced travel times between key points, and interviews revealed that 66% of respondents were satisfied with traffic improvements. While acknowledging the positive impacts of new road connections in decreasing travel time and improving accessibility, the study found that residents of informal areas are seeking safer design and more effective traffic management in future transportation improvement projects.